KEY QUALITIES OF MANAGERS IN MODERN BUSINESS MODELS - Huatibieke, Telike; Sansyzbaeva, Galiya; Ashirbekova, Laura (Farabi Journal of Social Sciences, 2025)
Purpose. This paper explores the essential qualities of managers that determine the success and adaptability of modern business models in a rapidly changing environment. The study aims to highlight how managerial characteristics—such as emotional intelligence, adaptability, communication, and decision-making—serve as core factors influencing strategic direction and corporate development. Special attention is given to the growing role and impact of female managers. Design/methodology/approach. The article employs a conceptual approach based on a review of relevant literature and theoretical perspectives. It provides a structured analysis of how different managerial traits contribute to business model optimization and organizational performance in modern economic contexts. Findings. The analysis confirms that personal qualities of managers are key to achieving operational efficiency, long-term sustainability, and cultural development within organizations. Furthermore, the inclusion of female managers enhances the diversity of leadership styles, enriches business strategies, and enables enterprises to better respond to multifaceted market demands. Originality. The study contributes to the discourse on business model development by emphasizing the underexplored yet central role of managerial personality traits. It also adds to gender-focused research by illustrating the unique value that women bring to contemporary leadership and strategic innovation. Key words: personal quality of managers, business model, decision-making power, emotional intelligence, communication ability, adaptability